Fungi, fungicide discovery and global food security - Steinberg, Gero (Fungal Genet Biol, 2020)
Securing sufficient food for a growing world population is of paramount importance for social stability and the well-being of mankind. Recently, it has become evident that fungal pathogens pose the greatest biotic challenge to our calorie crops. Moreover, the loss of commodity crops to fungal disease destabilises the economies of developing nations, thereby increasing the dimension of the threat. Our best weapon to control these pathogens is fungicides, but increasing resistance puts us in an arms race against them. New anti-fungal compounds need to be discovered, such as mono-alky lipophilic cations (MALCs) described herein. Collaborations between academia and industry are imperative to establish new and efficient ways to develop these new fungicides and to bring them to the market-place.